Comparison between Cinta Senese and Mora Romagnola crossed with Large White pigs - Sirtori F.; Crovetti A.; Campodoni G.; Bozzi R.; Franci O. (7th International Symposium on the Mediterranean Pig, 2012)
The recovery of the "Prosciutto del Casentino", a typical product of the homonymous area located in the Arezzo province, led to the constitution, during 2007, of the "Consorzio del Prosciutto del Casentino". One of the main rules of the Consortium imposes the use of the cross between both Large White or Landrace with the Cinta Senese or Mora Romagnola autochthonous breeds. This first trial foreseen the comparison between two of the possible types of crossbreeding, in reason to the fact that the crossing between Cinta Senese and Large White is well investigated whereas information on the crossing between Mora Romagnola and Large White is lacking. Two different types of crossbreed have been compared for both in vivo and post mortem performances. Chemical-physical characteristics of raw meat and fat have been determined whereas the hams are at present during the seasoning period. MRxLW subjects produced fatter carcasses with higher thickness of subcutaneous fat than CSxLW (33.8 vs 22.9 mm). Sample joint of MRxLW showed higher fat and lower lean percentage than CSxLW (37.6 vs 25.2; 54.4 vs 64.7). As regards chemical-physical analyses it emerges that the meat of the CSxLW presented higher percentage of moisture (74.30 vs 72.71) and more water losses for pressure (100.05 vs 67.74 mm2) than MRxLW.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)